Diphtheritic Polyneuropathy: A Rare Complication that Needs to be Acknowledged - Fandy Ong Jaya; Priscilla Love Lee; Kiking Ritarwan (Publication Department, Universitas Warmadewa, 2024)
Globally, diphtheria still poses a burden on public health, predominantly in developing countries. Poor vaccine coverage and boosters are the main factors in the diphtheria outbreak that should have been obliterated as the vaccine was invented a century ago. Health services are particularly burdened by diphtheria because it can lead to both short-term complications like acute airway obstruction and long-term complications like myocardial toxicity and diphtheritic polyneuropathy. Data about diphtheritic polyneuropathy is scarce, and physicians may not be aware of this condition. Herein we present the pathophysiology, clinical manifestation, diagnosis, and treatment of diphtheritic polyneuropathy.